Halal Lifestyle in the Covid-19 Pandemic - Firman Menne; Waspada Santing; Zulkifli Makkawaru; Tohir Mabruri (Perhimpunan Intelektual Muslim Indonesia, 2022)
The Covid-19 pandemic has had a negative impact on efforts to build a Halal lifestyle with the nation's economy slowing down, negative cash flow for a number of companies, increasing unemployment and poverty. This study aims to see and analyze the concept of a halal lifestyle in the life of the Muslim community in Indonesia, including during the Covid-19 pandemic. The research method used is a qualitative descriptive approach to explain some of the phenomena of the halal lifestyle in Indonesia which has been growing to date, complemented by a literature review based on several previous research results. The results show that, even though the Covid-19 pandemic is endemic, the halal lifestyle has first manifested itself in the halal ecosystem and has colored almost all aspects of the life of the Muslim community, this has happened with the presence of the Halal Product Guarantee Law and the Job Creation Law. These two laws and technical regulations derived from them, strengthen the guarantee of halal products and services, as well as halal and thayyibah businesses. Although it cannot be denied that there are obstacles in implementing a halal lifestyle in society